PERUBAHAN TEKS DALAM NOVEL GENI JORA KARYA ABIDAH EL KHALIEQY TERBITAN MAHATARI DAN QANITA - Amanda Maharani; Novi Diah Hariyanti (MEDAN MAKNA: Jurnal Ilmu Kebahasaan dan Kesastraan, 2022)
Abidah El Khalieqy's work entitled Geni Jora has different publishers namely, Mahatari and Qanita. Geni Jora's novel raises the issue of women who always come second after men. The figure of Kejora is here to erase these stigmas. However, the writer sees that there are differences in the words and sentences of several characters in the texts published by Mahatari and Qanita. In addition, there are also spelling differences in the two publications. Therefore, the purpose of this study is to look at the text changes that occurred in the two publications. Using a literary sociology approach related to the publisher and its ideology. The method used is qualitative analysis by reading, recording and classifying techniques. The results showed that there were differences in the contents of the two publications. Mahatari and Qanita as publishers have their own strengths and weaknesses.